Elaeagnus umbellata fruit - chemical composition, bioactive compounds, and kinetic of DPPH inhibition compared to standard antioxidants - Zglińska, Klara; Galewska, Anna Rygalo; Bryś, Joanna; Koczoń, Piotr; Borek, Kinga; Roguski, Mateusz; Niemiec, Tomasz (Emirates Journal of Food and Agriculture, 2021)
umbellata (Autumn Olive) is a medicinal plant used in traditional Asian medicine. In this study, we examine E. umbellata, which grows in central Europe (Poland). Despite significant climatic differences in both regions, we show that the fruits have a similar chemical composition and antioxidant activity to those observed in their native areas. For the first time, we examined the fatty acid composition of E. umbellata, showing that unsaturated fatty content for as much as 88.67% of total fat. Including the content of essential polyunsaturated fatty acids was over 50% of the total fat. We also examined proximate content, the content of fat-soluble vitamins, lycopene, beta carotene, and the mineral composition of the fruit. Moreover, using FT-IR spectrometry, we have shown that the fruits of the Autumn olive can change the distribution of chemical bonds when treated with hydrogen peroxide. The fruits of E. umbellata showed dose-dependent antioxidant properties with IC50 values of 76.27 µg / ml We also investigated the kinetic antioxidant activity of E. umbellata fruits based on DPPH radical inhibition compared to standard antioxidants (vitamin c and BHT). We have shown that using available protocols to spectrophotometrically study antioxidants' reaction with the DPPH radical may underestimate the effects of the Autumn Olive fruits.